An Investigation of Influence of Transition Arc Radius on the Tooth Root Crack Propagation - Wan Guoxin; Tang Jinyuan; Li Guowen; He Yuhui (Jixie chuandong)
The transition arc radius has an important influence on the root stress and root stress is an important influencing factor on the tooth root fatigue crack propagation,so that it is necessary to study the influence of transition arc radius on the tooth root crack propagation. Three kinds of spur gears with different transition arc radius are established and assume the root initial crack with same length in the same position,researching the tooth root crack propagation based on ABAQUS. The results indicate that,the root cracks with different transition arc radius have the same propagation trend,but larger transition arc radius with more extended to the deep crack direction gear rim in the early stage,larger transition arc radius with more extends to the top of the tooth in the later period. The transition radius has little influence on the critical crack length. Under the same crack length,the larger the transition radius with the smaller the Mises stress at the crack tip and the smaller the crack growth rate,the gear has the longer residual life.